2016
DOI: 10.1016/j.cjtee.2016.06.010
|View full text |Cite
|
Sign up to set email alerts
|

A distal-lock electromagnetic targeting device for intramedullary nailing: Suggestions and clinical experience

Abstract: PurposeTo describe our clinical experience with a system named SureShot™ Distal Targeting (Smith & Nephew, Memphis, USA) based on magnetic field presence and discuss our suggestions on this technique.MethodsWe analysed prospectively 47 patients affected by humeral, tibial or femoral fractures, treated in our institution during a 3-year period of time (August 2010 to September 2013). We considered the following parameters: the time to set up, the time to position a single screw, the effectiveness of the system … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 10 publications
(11 reference statements)
0
6
0
Order By: Relevance
“…Order of interlocking of nails with screws also dif- fer, some surgeons go for proximal locking irst and then to distal, whereas others do distal irst and then lock proximally. (Antonini et al, 2016;Caiaffa et al, 2016) In our study, all intertrochanteric fractures planned for short proximal femur nail with single headscrew and one distal locking screw were included, as of nailing for intertrochanteric fracture though technically similar but biomechanically and principle wise differs (Brin et al, 2014). In our study, we utilized only single C-arm for intra-operative luoroscopy throughout the procedure for all necessary views and steps.…”
Section: Resultsmentioning
confidence: 99%
“…Order of interlocking of nails with screws also dif- fer, some surgeons go for proximal locking irst and then to distal, whereas others do distal irst and then lock proximally. (Antonini et al, 2016;Caiaffa et al, 2016) In our study, all intertrochanteric fractures planned for short proximal femur nail with single headscrew and one distal locking screw were included, as of nailing for intertrochanteric fracture though technically similar but biomechanically and principle wise differs (Brin et al, 2014). In our study, we utilized only single C-arm for intra-operative luoroscopy throughout the procedure for all necessary views and steps.…”
Section: Resultsmentioning
confidence: 99%
“…Neurovascular and/or tendon damage, breaking of the drill, and bleeding have been reported during the distal locking stage in the treatment of humeral shaft fractures with conventional nails. [ 3 , 7 , 8 , 17 , 18 ] The distal humerus is rich in neurovascular anatomic structures; therefore, percutaneous distal locking may cause risks during conventional nailing. In their studies on cadaveric bones, Rupp et al[ 19 ] reported that the radial nerve is in direct risk in conventional nailing techniques where the distal locking is placed from lateral to medial in accordance with nail design.…”
Section: Discussionmentioning
confidence: 99%
“…In conventional nailing, the freehand technique for distal locking makes surgery difficult, while prolonging the duration and increasing radiation exposure. [ 8 , 9 , 17 ] Electromagnetic guided targeting systems have been developed to reduce these problems in conventional nails. In the literature, there are few studies reporting the results of electromagnetic systems in patients who underwent intramedullary nailing for humerus fractures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations